Routine kidney variables, glomerular filtration rate and urinary cystatin C in cats with diabetes mellitus, cats with chronic kidney disease and healthy cats. Issue 10 (October 2015) - Paepe, Dominique; Ghys, Liesbeth FE; Smets, Pascale; Lefebvre, Hervé P; Croubels, Siska; Daminet, Sylvie
Objectives: Diabetic kidney disease (DKD) is a frequent and serious complication in human diabetic patients, but data are limited in cats. This study was undertaken to assess whether diabetic cats are susceptible to DKD. Methods: Kidney function was compared between 36 cats with diabetes mellitus (DM), 10 cats with chronic kidney disease (CKD) and 10 age-matched healthy cats by measuring routine kidney variables (serum creatinine [sCreat], serum urea [sUrea], urine specific gravity [USG], urinary protein:creatinine ratio [UPC]), urinary cystatin C:creatinine ratio and glomerular filtration rate (GFR). Urinary cystatin C (uCysC) was measured with a human particle-enhanced nephelometric immunoassay, validated to measure feline cystatin C, in all but two diabetic cats. GFR was evaluated by exo-iohexol clearance in 17 diabetic cats, all cats with CKD and all healthy cats. Results: Diabetic cats had significantly (mean ± SD) lower sCreat (123 ± 38 vs 243 ± 80 µmol/l), sUrea (11 ± 3 vs 18 ± 7 mmol/l) and urinary cystatin C:creatinine ratio (6 ± 31 vs 173 ± 242 mg/mol), and a significantly higher USG (1.033 ± 0.012 vs 1.018 ± 0.006) and GFR (2.0 ± 0.7 vs 0.8 ± 0.3 ml/min/kg) compared with cats with CKD. Compared with healthy cats, diabetic cats only had significantly lower USG (1.033 ± 0.012 vs 1.046 ± 0.008). Proteinuria (UPC >0.4) was present in 39% of diabetic cats, in 30% of cats with CKD and in none of the healthy cats. However, the UPC did not differ statistically between the three groups. Conclusions and relevance: Based on evaluation of routine kidney variables, GFR and uCysC as a tubular marker at a single time point, a major impact of feline DM on kidney function could not be demonstrated.